2020
DOI: 10.21037/atm-2020-cass-17
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of the extracranial carotid artery in tandem lesions during endovascular treatment of acute ischemic stroke: a systematic review and meta-analysis

Abstract: Endovascular treatment (EVT) is the standard treatment for patients with an acute ischemic stroke due to occlusion of large vessel occlusion (LVO). In 20% of patients, concomitant extracranial internal carotid artery (EICA) lesion is present. These tandem lesions (TL) offer a technical challenge. The treatment strategy for the treatment of the ipsilateral EICA is unclear. The aim of this review is to compare two treatment strategies for TL during EVT: balloon angioplasty (BA) only and immediate carotid artery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 56 publications
3
21
0
1
Order By: Relevance
“…We found no association between the early start of DAPT and SICH occurrence (see Results), which was in line with previous finding of no increase in SICH associated with DAPT resulting from recent large meta-analyses [ 14 , 24 ], however, we cannot exclude a potential bias representing by a fact that in some of our patients, the control CT was done earlier than the start of DAPT after EVT, and thus if ICH/SICH was present on control CT, DAPT was not started at all, or antiplatelet monotherapy was used only.…”
Section: Discussionsupporting
confidence: 93%
“…We found no association between the early start of DAPT and SICH occurrence (see Results), which was in line with previous finding of no increase in SICH associated with DAPT resulting from recent large meta-analyses [ 14 , 24 ], however, we cannot exclude a potential bias representing by a fact that in some of our patients, the control CT was done earlier than the start of DAPT after EVT, and thus if ICH/SICH was present on control CT, DAPT was not started at all, or antiplatelet monotherapy was used only.…”
Section: Discussionsupporting
confidence: 93%
“…We did not find a difference in the rate of sICH between patients with prior IVT and with EVT alone (table 2), and the overall rate of sICH (6.2%) was similar to the rates reported from the TITAN and ETIS registry (8.1%)9 and from recent large meta-analysis 18 21. Our findings, as well as those from previous reports, suggest that IVT before EVT seems to be safe,18 22–24 even in patients with TL9 12; however, patients treated with EVT alone may have a lower risk ratio for any type of ICH compared to those treated with bridging therapy 18…”
Section: Discussionsupporting
confidence: 85%
“…In a systematic review and meta-analysis of 16 cohort studies of tandem lesion patients treated with EVT and CAS or PTA for concomitant extracranial carotid lesions, the incidence of severe intracranial haemorrhage was 8%. 25 Immediate CAS may not be technically feasible in all patients and CEA may offer an advantage compared with CAS in patients with increased risk of bleeding from DAPT, such as those with a history of gastrointestinal bleeding. In a small series, Singh et al found that emergency CEA had less intracranial haemorrhage than emergency CAS.…”
Section: Discussionmentioning
confidence: 99%